EXPLORING ENGLISH FOR SPECIFIC PURPOSES NEEDS’ FOR UNDERGRADUATE PSYCHOLOGY STUDENTS - Farhah Syaufika; Evi Karlina Ambarwati (IKIP Siliwangi, 2023)
This research was investigated the needs of psychologist students towards English, so that the target context in their respective fields can be achieved well. The aims of this study is to analyze the needs of English for Specific Purpose in psychology students. This study used qualitative descriptive research design to describe the needs of ESP in student psychologists. This research conduct using an Online Questionnaire method with Google Form as tool or media to facilitate the collection of research data to made data collection easier. The questionnaire contained questions divided into five main sections; a) Target Situation Analysis, b) Discourse Analysis, c) Present Situation Analysis, d) Learner Factor Analysis, and e) Teaching Context Analysis. Participants in this study numbered 10 respondents who were undergraduate students of psychology at one of the universities in Jakarta. The result of this study showed that ESP course can affect English proficiency in psychologist students. Most of psychology students need English to communication with their friend nor their lecturer. This research is useful for teachers and ESP students in understanding and creating new teaching materials for English subjects in other fields so that the scope of English material is wider.